Evaluation of Prosopis Africana Gum in the Formulation of Jellies (Journal of Science and Technology, 2016)
Prosopis gum has been evaluated for use in the formation of jellies. The percentage of salicylic acid released from jellies prepared from prosopis was investigated. The percentage of permeation of drug through the jelly was also investigated. Surfactants were incorporated into the gels and the effect on the release and permeation also investigated.The release of salicylic acid from the jellies was low. Similarly, the quantity of the drug thus permeated through the jelly was also low. Incorporation of Surfactants did not enhance the release of the drug. The low release and permeation rate may be due to the poor water solubility of the incorporated drug.Correlation of the quantity of drug released with viscosity shows that drugs released was dependent on the viscosity of the jellies, the highly viscous jellies showing lower release.